The Concept Of Gender Justice And Women’s Rights In Nigeria: Addressing The Missing Link - Odiaka, Ngozi Oluchukwu (Journal of Sustainable Development Law and Policy, 2025)
Over the years, Nigeria has gained the unpopular recognition globally as a patriarchal society in which the inalienable rights of women are often subjected to ridicule, extensive abuse, neglect and violations. Cultural, religious and societal norms have arguably entrenched a historical imbalance in power relationships between men and women and have tilted the overall perceptions and roles of women in Nigeria. In Nigeria, it could be said that the abuse of the natural rights of a woman begins from the time of her birth and only comes to an end at the time of her death. In many parts of Nigeria, particularly the North, women who are prematurely and compulsorily betrothed to a man at birth are not allowed access to basic education and are generally burdened with domestic household chores. These becomes the foundation for a lifetime of circular and absolute dependence on a man she does not know: and upon the demise of the man her right to inherit his property is denied and her life becomes miserable because of obnoxious practices which she could be made to undergo as a sign of respect for the deceased husband. These cultural, religious and societal norms are arguably at the root of the historical neglect of women in Nigeria. The rapid ascendancy of human rights in Nigeria, coupled with Nigeria’s prominent role as a signatory to virtually all the core international human right treaties and instruments raised expectations that women in Nigeria may begin to enjoy some measure of protection from archaic and anachronistic practices that subject them to a wanton abuse. The scope of these happenings requires an extensive reflection and worthy of scholarly examination in the light of recent debates in the Nigeria National Assembly on child marriage, women’s right and the need for constitutional protection for the girl child. This paper examines the nature, scope and extent of human rights protection afforded to women under Nigerian domestic laws and under international law. It reflects on how key issues such as child marriage, women’s property rights and female succession norms and practices affect gender justice and the protection and fulfillment of the rights of women in Nigeria. It discusses the possible legal panacea to these historical and cultural challenges in this 21st century.